2016
DOI: 10.5539/ijb.v8n2p85
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mutagenic Effects of Synthetic Acidic Textile Dyes by Umu-Test (Salmonella thyphimurium TA1535/pSK1002)-a Short Term Bacterial Assay

Abstract: <p class="1Body">In this study, genotoxic properties of some synthetic acidic dyes were researched by <em>umu</em>-test (<em>Salmonella thyphimurium </em>TA1535/pSK1002) which is a short term bacterial test. The study analyzed genetoxic activity of Acid Blue 127, Acid Orange 51, Acid Black 63, Acid Yellow 17 and Acid Blue 113 synthetic acidic dyes in presence and absence of S9 fraction used in Textile industry. Solutions of dyes at concentrations of 400 µg/ml, 120 µg/ml, 40 µg/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Wastewater from these industries is dangerous to the environment and human health since it has been demonstrated that synthetic dyes are toxic, mutagenic and/or carcinogenic. Moreover, these compounds can cause allergies and dermatitis [ 183 , 188 ].…”
Section: Bioremediation By White Rot Fungimentioning
confidence: 99%
“…Wastewater from these industries is dangerous to the environment and human health since it has been demonstrated that synthetic dyes are toxic, mutagenic and/or carcinogenic. Moreover, these compounds can cause allergies and dermatitis [ 183 , 188 ].…”
Section: Bioremediation By White Rot Fungimentioning
confidence: 99%
“…The effluents from these industries are highly colored, which reduces the amount of sunlight available to photosynthetic organisms which leads to diminished oxygen levels in aquatic ecosystems (Kirst et al, 2004;Vasdev K., 2015). Wastewaters from these industries pose a threat to the general environment and also for human health since some dyes are toxic, mutagenic and potentially carcinogenic (Vasdev, 2015;Senel et al, 2016). Moreover, synthetic dyes are very stable to light, temperature and microbial attack, making them recalcitrant compounds that accumulate in ecosystems (Levin et al, 2010;Plácido et al, 2016).…”
Section: Introductionmentioning
confidence: 99%